Method and system for detecting and classifyng the mental state of a subject (2005)
A method of detecting and classifying mental states, comprising the steps of: detecting bio-signals from one or more than one bio-signal detector; transforming the bio-signals into one or more than one different representations; detecting values of one or more than one property of the transformed bio-signal representations; and applying one or more than one mental state detection algorithm to the detected properties in order to classify whether the bio-signals indicate the presence of a predetermined response by a subject.